Effects of commercial microbial products on water quality in tropical shrimp culture ponds - Matias-Peralta, Hazel Monica; Md. Yusoff, Fatimah; Mohamed Din, Mohamed Shariff; O., Azhar (Asian Fisheries Society, 2002)
A study was conducted to compare the efficacy of different microbial products in enhancing the water quality of commercial shrimp grow-out ponds. A total of nine ponds, with three ponds for each treatment designated as T1 (Product 1), T2 (Product 2) and control were used. Physical and chemical parameters of pond water were analyzed fortnightly throughout the culture cycle of 110 days. Pore water of the pond bottom sediment, collected on days 45 and 100 of culture, was analyzed for the same parameters. Total ammonia N, nitrite-N, nitrate-N, total nitrogen, and hydrogen sulphide increased steadily with the culture period in T1 and T2 ponds. Similarly, nutrient concentrations in the pore water increased significantly (P < 0.05) from the beginning to the end of the culture cycle except for the dissolved silica, which decreased significantly (P < 0.05) during the same period. Water transparency was highest during the initial phase of culture but gradually declined towards the end of the cycle. Total nitrogen and ammonia concentrations in T1 were lower than those in other treatments in the first two phases of the culture period. Values of all other physical and chemical parameters were not significantly different (P > 0.05) among treatments. In this study, the addition of commercial microbial products to shrimp ponds did not result in significant improvement of water quality over the control. However, relatively better water quality in the early phase of the culture period and higher shrimp production in T1 ponds indicated that certain microbial products have the potential to enhance pond environment and shrimp yields.